1995
DOI: 10.1093/infdis/171.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases and Human Immunodeficiency Virus Control in Malawi: A Field Study of Genital Ulcer Disease

Abstract: Men with genital ulcer disease (GUD) attending a clinic in Malawi were evaluated and treated with one of five drug regimens. Haemophilus ducreyi was isolated from 204 (26.2%) of 778 patients. Of 677 men, 198 (29.2%) had treponemes detected in ulcer material by direct immunofluorescence or had rapid plasma reagin reactivity of > or = 1:8. Human immunodeficiency virus type 1 (HIV-1) seroprevalence was 58.9% overall and 75.8% among patients reporting a history of GUD (P < .001). By logistic regression analysis, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 6 publications
1
38
1
Order By: Relevance
“…That the sensitivity of virus isolation varies with ambient temperature is of more than local interest. A review of the literature on genital ulcer disease in tropical countries in which only viral culture was used has shown a relatively low frequency of HSV as an etiology of genital ulcer disease (GUD), even in populations in which HSV-2 seroprevalence was high [19][20][21][22]. Morerecent studies that used PCR-based methods have shown that HSV is the most frequent cause of GUD in these regions of the world [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…That the sensitivity of virus isolation varies with ambient temperature is of more than local interest. A review of the literature on genital ulcer disease in tropical countries in which only viral culture was used has shown a relatively low frequency of HSV as an etiology of genital ulcer disease (GUD), even in populations in which HSV-2 seroprevalence was high [19][20][21][22]. Morerecent studies that used PCR-based methods have shown that HSV is the most frequent cause of GUD in these regions of the world [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Studies done on STIs have been mainly on selected populations such as females attending gynaecological, obstetric, and family planning clinics, STI clinic attenders, and among female sex workers. [3][4][5] Findings from such studies cannot be generalised to general populations in whom most STIs are either unrecognised or asymptomatic. The scarcity of accurate data is consequently a handicap in designing appropriate control measures.…”
Section: Introductionmentioning
confidence: 93%
“…An STI results in an increase in genital HIV viral load, which means that having sex with a person with an STI implies an exposal to a higher viral load (88). Furthermore, STIs also result in the recruitment of macrophages and lymphocytes which are virotrophic (87)(88)(89)(90)(91)(92). A person with STI and exposed to HIV infection through sex is likely to acquire the infection due to the breached epithelium and/or increase in white cells to which HIV will get attached for entry.…”
Section: Treatment Of Stismentioning
confidence: 99%